Helena Attlee: The Land where Lemons Grow: the Story of Italy and its Citrus Fruit - Hyman, Clarissa (Petits Propos Culinaires, 2014)
Helena Attlee: The Land where Lemons Grow: the Story of Italy and its Citrus Fruit: Particular Books, 2014: 272 pp., hardback, £20.00.